2018
DOI: 10.1007/s40477-018-0297-2
|View full text |Cite
|
Sign up to set email alerts
|

Automated classification of focal breast lesions according to S-detect: validation and role as a clinical and teaching tool

Abstract: S-detect is a feasible tool for the characterization of breast lesions; it has a potential as a teaching tool for the less experienced operators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
74
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 30 publications
5
74
0
1
Order By: Relevance
“…S-detect™ is a recently developed breast cancer CAD system using deep-learning algorithm with big data which providing assistance in morphological analysis by the ACR BI-RADS (4, 5, 9-12). Several studies have reported that S-detect™ could enhance the diagnostic performance of radiologists (5,6,(9)(10)(11)(12)14). In addition, several studies have published that S-detect™ is a useful diagnostic tool that could be clinically used to enhance the specificity, PPV, and accuracy of breast US, regardless of the degree or radiologist's experience (9,12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S-detect™ is a recently developed breast cancer CAD system using deep-learning algorithm with big data which providing assistance in morphological analysis by the ACR BI-RADS (4, 5, 9-12). Several studies have reported that S-detect™ could enhance the diagnostic performance of radiologists (5,6,(9)(10)(11)(12)14). In addition, several studies have published that S-detect™ is a useful diagnostic tool that could be clinically used to enhance the specificity, PPV, and accuracy of breast US, regardless of the degree or radiologist's experience (9,12).…”
Section: Discussionmentioning
confidence: 99%
“…Our study aimed to determine the merits of the CAD system in breast US reading using breast phantom. In one previous study, five readers including residents retrospectively reviewed the CAD images and gave their assessments; inter-rater agreement was measured with Cohen's kappa value (11). The conclusion of that study was that S-detect™ is a feasible tool for characterization of breast le-sions; it has a potential as a teaching tool for the less experienced operators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S-Detect™ for Breast is a cutting-edge CAD system that acts as an assistant tool for US imaging diagnosis of breast lesions. The diagnostic e cacy of the CAD software for classifying breast lesions has been validated by several studies [19][20][21] . Furthermore, S-Detect™ has been proven to be of value in increasing the diagnostic performance of the in-training residents 19,22 .BI-RADS 4a lesions posed a potential challenge for breast US.…”
mentioning
confidence: 99%
“…The diagnostic e cacy of the CAD software for classifying breast lesions has been validated by several studies [19][20][21] . Furthermore, S-Detect™ has been proven to be of value in increasing the diagnostic performance of the in-training residents 19,22 .BI-RADS 4a lesions posed a potential challenge for breast US. And as far as we know, the feasibility of S-Detect™ in improving the diagnostic accuracy of the residents-in-training in BI-RADS 4a lesions has not been investigated by previous studies.…”
mentioning
confidence: 99%